2022
DOI: 10.1142/s2301385023500073
|View full text |Cite
|
Sign up to set email alerts
|

Real-time 3D UAV Path Planning in Dynamic Environments with Uncertainty

Abstract: The integration of Unmanned Aerial Vehicles (UAVs) is being proposed in a spectrum of applications varying from military to civil. In these applications, UAVs are required to safely navigate in real-time in dynamic and uncertain environments. Uncertainty can be present in both the UAV itself and the environment. Through a literature study, this paper first identifies, quantifies and models different uncertainty sources using bounding shapes. Then, the UAV model, path planner parameters and four scenarios of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The route planning in the study area is carried out using the UAV-airborne LiDAR adaptive route planning method proposed in this paper in terms of the first stable iteration time, the total time required for the same number of iterations, the route length, and the vegetation coverage within the sample corresponding to the route nodes. Comparing the results of different route planning, it can be concluded that (1) The route planning method proposed in this paper has a faster iteration speed compared with the classical ant colony algorithm, that is, it takes less time cost to complete a route planning and has a higher optimization capability. And the vegetation coverage of the flight area can be taken into account, and the location nodes with lower vegetation coverage can be selected to complete the route planning.…”
Section: Route Planning Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The route planning in the study area is carried out using the UAV-airborne LiDAR adaptive route planning method proposed in this paper in terms of the first stable iteration time, the total time required for the same number of iterations, the route length, and the vegetation coverage within the sample corresponding to the route nodes. Comparing the results of different route planning, it can be concluded that (1) The route planning method proposed in this paper has a faster iteration speed compared with the classical ant colony algorithm, that is, it takes less time cost to complete a route planning and has a higher optimization capability. And the vegetation coverage of the flight area can be taken into account, and the location nodes with lower vegetation coverage can be selected to complete the route planning.…”
Section: Route Planning Results and Discussionmentioning
confidence: 95%
“…At present, for the route planning problem, the research is generally focused on the improvement of classical route planning algorithms, such as the improvement of the A* algorithm, 1 classical ant colony algorithm, 2 , 3 and particle swarm algorithm 4 . In addition, there are also new algorithms inspired by existing algorithms are proposed, such as the gray wolf optimization algorithm, 5 the bat optimization algorithm, 6 and the differential evolution algorithm 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They used the same cell decomposition as previous studies and implemented the GRASP-VND (greedy randomized adaptive search procedure-variable neighborhood descent) algorithm [12]. Zammit et al also conducted a study to identify the cause, define different path scenarios, and verify their performance using A* and RRT algorithms to solve the problem of UAVs having to fly in real time in an environment with high uncertainty [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the combination of the perceptual advantage of deep learning and the decision-making ability of reinforcement learning has been applied in various control systems Error! Reference source not found., [11],Error! Reference source not found.Error!…”
Section: Introductionmentioning
confidence: 99%